EFFECTS OF ROUNDROBIN BRAINSTORMING AND THINK-PAIR-SHARE INSTRUCTIONAL STRATEGIES ON SECONDARY SCHOOL STUDENTS’ KNOWLEDGE, ATTITUDE AND PERCEIVED RISK OF HIV/AIDS IN OSUN STATE, NIGERIA (2014)
Literature have shown that students generally have erroneous knowledge about the transmission of HIV/AIDS which resulted in bad attitude that put them at risk of contracting the disease. There is a need to have instructional strategies that could help to increase the knowledge, attitude and perceived risk of HIV/AIDS in order to reduce the spread of the disease.There are dearth of studies on the importance of cooperative instructional strategies in changingsecondary school students’ knowledge, attitude and perceived risk of HIV/AIDS. This study was therefore designed to investigate the effects of Round robin Brainstorming (RRB) and Think-Pair-Share (TPS) instructional strategies on secondary school students’ knowledge, attitude and perceived risk of HIV/AIDS in Osun State, Nigeria. The moderating effects of students’ socioeconomic background and gender were also examined.The pretest-posttest, control group quasi experimental design with 3x3x2 factorial matrix was adopted. Four hundred senior secondary school 1 students were randomly selected from eight co-educational public secondary schools in Ife Central and Ife East Local Government Areas of Osun State. They were assigned into Roundrobin Brainstorming, Think-Pair-Share and control groups respectively. The study lasted eight weeks. The research instruments used were:Achievement Test on HIV/AIDS (0.77), Students HIV/AIDS Attitude Questionnaire (0.78),Students Perceived Risk of HIV/AIDS Questionnaire (0.78), Students Socio-economic Background Questionnaire (0.78), Roundrobin Brainstorming and Think-Pair-Share Instructional guides and Performance Assessment form. Seven null hypotheses were tested at 0.05 level of significance. Data collected were analysed using ANCOVA and Scheffe post-hoc test. There was a significant main effect of treatment on students’ knowledge of HIV/AIDS (F(3,396) = 135.87; η2 = .42). Students exposed to TPS performed best (𝑥̅ = 90.63) followed by those in RRB (𝑥̅ = 77.01) and control group (𝑥̅ = 66.68) respectively. There was a significant main effect of treatment on students’ attitude to HIV/AIDS (F(3,396) = 233.15; η2 =.55). Students exposed to TPS had a higher post-attitude test (𝑥̅ = 62.05) than RRB (𝑥̅ = 51.97) and the control group (𝑥̅ = 42.21). There was a significant main effect of treatment on students’ perceived risk of HIV/AIDS (F(3,396) = 269.67; η2 =.59). Students exposed to TPS had the highest posttest mean score of perceived risk (𝑥̅ = 68.65) followed by those in RRB (𝑥̅ = 54.99) and control group (𝑥̅ = 41.18). Socio-economic background had a significant main effect on students’ knowledge (F(3,396) = 136.33; η2 = .03), attitude (F(3,396) = 6.70; η2 =.03) and perceived risk (F(3,396) = 7.49; η2 =.04). This shows that socio-economic background could positively influence student’s performance. Students’ scores on knowledge, attitude and perceived risk on HIV/AIDS were not significant regardless of sex. The Roundrobin Brainstorming and Think-Pair-Share instructional strategies enhanced secondary school students’ knowledge, attitude and perceived risk of HIV/AIDS. These strategies should be used in schools by teachers in order to improve students’ knowledge, change their attitudes and create awareness to curtail the spread of HIV/AIDS